The Role of Public Administrators in Building a Robust Liberal Democracy - Eva Sørensen; Jacob Torfing (Public Administration Review, 2026)
ABSTRACT After decades of expansion, liberal democracy is threatened by autocratic populists. These actors exploit widening gaps between leaders and citizens, as well as growing political polarization in the population, to consolidate executive power by undermining courts, sidelining elected assemblies, discrediting public administrators, and intimidating both opposition and the press. This alarming predicament begs the question of what enterprising role public administrators can play in curbing the rise of autocratic populism by reconnecting elected politicians with diverse and polarized population groups while fostering alignment among them. To this end, public administrators are conceptualized as bridgebuilders promoting interactive political leadership along the vertical axis of the political system; as mediators fostering agreement, accommodation, or compromise between polarized groups along the horizontal axis; and as institutional architects linking representative democracy and collaborative governance arenas. This expanded role of public administrators as democratic guardians and protagonists raises important questions regarding its legitimacy.